Development of analysis method of andrographolide from Andrographis paniculata using UPLC-PDA - Syefira Salsabila; Diah Astari Salam; Sumail Sidik Ode Ishak; Amrianto (Current Research on Bioscences and Biotechnology, 2023)
Andrographis paniculata is an herbaceous plant belonging to the family Acanthaceae dan also known as the â€œKing of Bittersâ€. It has been utilized as traditional medicines by the local people in India and Southeast Asia. Many studies have been reported regarding the pharmacological activities of A. paniculata and Andrographolide. Currently, in addition to compound isolation and bioactivity assays, validation of analysis method is also required. Validation is used to demonstrate that the method used is appropriate and the results are precise and accurate. The method used needs to be simple, concise, precise, accurate, and widely used. The analysis in this study was carried out using Ultra-Performance Liquid Chromatography because the instrument operates at high pressure. In addition, the system uses fine particles which can reduce column length as well as solvent and time consumption. This study aims to validate analytical methods in determining the contents of andrographolide in an A. paniculata Leaves. The analytical method was validated through a Waters Alliance UPLC System with photodiode array (PDA) detector. The A. paniculata extract and standard solutions of Andrographolide were analyzed using reverse-phase C18 column which was maintained at 40Â°C. A mobile phase of 0.1% formic acid in acetnotirile and 0.1% formic acid in water was used at flow rate of 0.3 mL/min to achieve gradient elution. The linearity of the andrographolide showed excellent results (R2= 0.9999) in the concentration range of 7.8â€“250.0 Âµg/mL. The LOD and LOQ values of andrographolide were 0.068 Âµg/mL and 0.205 Âµg/mL, respectively. The intra-day and inter-day relative standard deviation (RSD) and relative error (RE) accuracy values of andrographolide were <Â±15. The quantitative analysis found that A. paniculata extract contained 12.45 Â±0.06 mg/g of Andrographolide. This developed UPLC-PDA method was proven to be precise, specific, sensitive, and accurate for routine quality assessment of raw material of Andrographis paniculata leaves content.